Perceptions of nursing students and nursing faculty about incivility and its factors in nursing education: A descriptive qualitative study - Ali, Bibi Hajira Irshad; Dhamani, Khairunnisa Aziz; Rizvi, Naghma (Journal of Shifa Tameer-e-Millat University, 2022)
Introduction: Incivility is commonly observed in number of schools including nursing institutions around the world. It affects both, students and faculty members by interrupting class discipline and the learning environment. Thus, understanding the factors leading to incivility in nursing college will assist in identifying strategies to deal with the problem. Objective: To explore the perceptions of nursing students and faculty members about incivility and its factor in nursing education. Methodology: A qualitative descriptive design was used and participants, from a private college of nursing Islamabad, Pakistan, were recruited through purposive sampling. One on one in-depth interview was conducted with five faculty members and 12 students using an open-ended interview guide. Using content analysis, codes were identified and similar codes formed the categories and theme evolved from the categories. Results: Data analysis generated a description of incivility, uncivil behaviors, factors causing incivility, and strategies to overcome incivility as categories. The most leading factors of incivility were the lack of teaching-learning strategies and the socio-cultural and family background of students. The strategies that suggested overcoming incivility were orientation sessions, professional development activities, and developing policies to reduce incivility in the institution. Conclusion: For improving civility in nursing college, insight about incivility among students and faculty members is to be developed and policies to be in place to address unacceptable behaviors in a timely and effective manner.